Effects Of 5E Guided Learning With Graphing Calculator On Form Four Students Achievement And Higher Order Thinking Skills In The Topic Graphs Of Functions II - Muthiah, Jeyaletchumi (2020)
The aim of this research is to investigate the effect of incorporating graphing calculator on students Achievement and Creative Design with graphing calculator (creativity is the highest level in HOTS). The focus of the study is Chapter 2: Graphs of Functions II from the upper secondary Mathematics syllabus. 108 Form four students from three urban secondary schools in Penang were the respondents. (Experimental group 1, n = 36; Experimental group 2, n = 36 and control group n = 36). The independent variable was the teaching and learning of Graphs of Functions II incorporating graphing calculator with three different approaches.